Decrypting molecular mechanism of heat stress tolerance in rice to tackle climate change challenges through recent approaches - Kumar, Neeraj; Khatibi, Seyed Mahdi Hosseiniyan; Sharma, Deepak; Azeem, Faraz; Koutu, Ganesh Kumar; Ali, Jauhar (Frontiers in Plant Science, 2026)
Rice (Oryza sativa) is one of the world’s most important cereal crops, contributing to food and financial security, particularly in developing countries. High temperature due to climate change seriously threatens sustainable rice production. Rice crops are adversely affected by heat stress at the morphological, physiological, and molecular levels, resulting in reduced yield and poor grain quality. Rice is highly sensitive to heat during the reproductive phase, causing pollen sterility, impaired pollen dehiscence, pollen germination, and tube growth, ultimately drastically reducing spikelet sterility and yield. High temperature also promotes the accumulation of reactive oxygen species in plant cells, resulting in multiple adverse effects, including damage to chloroplasts and cell membranes, inactivation of photosystems, reduced Rubisco activity, and impaired production of photoassimilates. In this review, we have synthesized the current knowledge on the effects of heat stress on rice and summarized QTLs, genes, and regulatory pathways underlying thermotolerance. We further evaluate conventional breeding, transgenics, and diverse omics-based strategies to breed high-yielding, heat-tolerant rice varieties. The precise molecular insights gained through various omics approaches are expected to advance our understanding of the intricate nature of heat stress tolerance in rice. Additionally, we highlight the emerging roles of microbiome, high-throughput phenotyping technologies, and artificial intelligence as promising tools for accelerating the development of heat-resilient rice.